1965
DOI: 10.1021/ja01084a047
|View full text |Cite
|
Sign up to set email alerts
|

A Marked Effect of Conformation in the Radiolysis of Poly-α-L-glutamic Acid in Aqueous Solution

Abstract: Sir :Compounds containing the peptide bond undergo chemical degradation at the N-C linkage on irradiation in aqueous solution under oxygen. The schematics of the radiation-induced reactions are given by'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1968
1968
2012
2012

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…65 With iV-acetylglutamic acid in oxygenated solution, mainchain degradation via reactions 14-18 to yield amide and a-ketoglutaric acid functions accounts for ~30 percent of the OH radicals. 68 The remainder attack at the side chain via Reactions akin to the degradation reaction 45 have been observed in other systems. 49 The unsaturated degradation product formed in reaction 45 corresponds to a class of compounds referred to as dehydropeptides.…”
Section: Aqueous Solutionmentioning
confidence: 90%
“…65 With iV-acetylglutamic acid in oxygenated solution, mainchain degradation via reactions 14-18 to yield amide and a-ketoglutaric acid functions accounts for ~30 percent of the OH radicals. 68 The remainder attack at the side chain via Reactions akin to the degradation reaction 45 have been observed in other systems. 49 The unsaturated degradation product formed in reaction 45 corresponds to a class of compounds referred to as dehydropeptides.…”
Section: Aqueous Solutionmentioning
confidence: 90%
“…208 Abstraction of hydrogen from the γ-(C-4) carbon of aliphatic side chains in the presence of oxygen can yield C-2-C-3 dehydropeptides, via the formation of peroxyl radicals from the γ-carbon-centered radical. 208,210 For example, in the oxidation of the Glu side chain, the γ-carbon peroxyl radical may undergo subsequent reactions leading to the formation of side chain modification products with a mass shift of -30 Da due to decarboxylation; 209,211 +14 and +16 Da products; or an unsaturated product, a C-2-C-3 dehydropeptide (Scheme 4). The dehydropeptide behaves like an oxygenated enol species, which readily undergoes tautomerism to the keto form.…”
Section: Main Chain Cleavage Via Radical Transfer From γ-Carbon At Si...mentioning
confidence: 99%
“…Garrison (1968) proposed destruction of model peptides via labile iminopeptides generated from peroxy radicals. The iminopeptide intermediates can be hydrolysed under conditions conventionally used to displace ammonia from amides [1 M-H2SO4 for 3 h at 100°C (Sokol et al, 1965)]. More recently, Schuessler & Schilling (1984) observed that fragments ofdefined length were produced from BSA by radiolytically generated OH'.…”
Section: Protein Fragmentation By H202mentioning
confidence: 99%